ЕНЕРГЕТИЧНІ ПОКАЗНИКИ ТОРЦЕВИХ ДУГОСТАТОРНИХ АСИНХРОННИХ ДВИГУНІВ З БІМЕТАЛЕВИМИ ДИСКОВИМИ РОТОРАМИ - Карлов, О.М.; Кондратенко, І.П.; Крищук, Р.С.; Ращепкін, А.П. (Інститут електродинаміки Національної академії наук України, 2017)
The method of calculating the energy indicators of an axial arc-stator induction motor (AAIM) with a bimetal disk rotor is presented. The mathematical model of the motor with accepted assumptions is presented. The model is developed on the basis of Maxwell's equations, takes into account linear speed of rotation. Using the Pointing theorem and three-dimensional representation of the magnetic field induction in the gap of motor, the analytical calculation of complete integrated power was performed. Expressions for calculating the main complex resistance of the engine, which includes the mutual interphase inductance, are done. Expressions for calculating the electromagnetic moment, the useful power, the efficiency factor, the power factor are presented. The method allows calculating energy indices both at given complex amplitudes of a current, and a voltage. References 5, figure, table.